The importance of subjective measurements in child and youth well-being studies - Thalia Hirsch; Britta Busse (Institut Arbeit und Wirtschaft (IAW), Universität Bremen und Arbeitnehmerkammer Bremen, 2020)
Considering changing political landscapes and societies' needs in Europe, we argue for establishing a European longitudinal study on child and youth well-being revealing new trends in a longterm perspective. As a part of an international research team, we worked on preparing this study, called EuroCohort. By doing so, we were concerned with choosing theoretical as well as measurement concepts to capture (child and youth) well-being in a way that is needed in order to shed light on Europe's future generation. In this paper, we present our considerations on suitable theoretical approaches and their interrelation to measurement concepts. Thereby, our focus lies on the question how subjective measurement concepts can provide added value to child and youth well-being surveys. Although the relevance of subjective measures of well-being is recognised, so far hardly any comparative and longitudinal studies have incor-porated corresponding indicators. This paper emphasises the need for implementing subjective meas-urements in studies on child and youth well-being, respecting their value for different well-being domains.
Keywords: 330